Exercise experiences among persons with multiple sclerosis living in the southeast of the United States. Issue 1 (11th January 2022) - Richardson, Emma V.; Barstow, Elizabeth; Motl, Robert W.
Abstract: Purpose: Exercise is one of the best behavioral approaches for improving health and wellbeing among persons with multiple sclerosis. The environment is a key influencer regarding engagement in this health enhancing activity among those with multiple sclerosis, yet existing research has often been restricted amongst Caucasian samples residing in the midwest and northwest of the United States, Europe and New Zealand. This study explored experiences of exercise among persons with multiple sclerosis from the southeast of the United States. Materials and methods: We interviewed 32 persons with multiple sclerosis from the southeast of the United States regarding exercise experiences, and then undertook an inductive, semantic thematic analysis. Results: The racially diverse sample of persons with multiple sclerosis in the southeast of the United States permitted a crafting of five themes that reflected lived experiences of exercise; (i) exercise is a therapeutic strategy, (ii) facilitators of exercise, (iii) barriers of exercise, (iv) ineffective exercise promotion, and (v) necessities for improved exercise promotion. Conclusion: Experiences of exercise in multiple sclerosis are transferable up to a point, but exercise interventions should be contextually specific depending on the geographic area and culture of persons with multiple sclerosis. Implications for Rehabilitation: Exercise is one of the only strategies that improves symptoms of multiple sclerosis and improves quality of life. Cultural and geographic climate may significantly influence exercise experiences, and subsequent engagement of exercise among persons with multiple sclerosis. Practitioners working with persons with MS in the southeast of the US should consider designing exercise programs that take into account the oppressive climate of this area. Persons' with MS cultural and geographic backgrounds should be considered when designing exercise programs to ensure more individualized and appropriate application.